Hedonistic Lifestyle Among College Students: A Comparative Study of Boarding House Residents vs. Family Cohabitants - Febryani, Annisa; Nasution, Fauziah (Yayasan Sembilan Pemuda Indonesia, 2025)
This research aims to examine the differences in hedonistic lifestyle between students living in boarding houses and those living with their parents at the State Islamic University of North Sumatra. The hedonistic lifestyle is characterized by an orientation towards the pursuit of pleasure, consumptive behavior, and a tendency to disregard efficiency and social functions. The approach used is a comparative quantitative design with an ex post facto format. The sample consists of 30 students, with 15 living in boarding houses and 15 living with their parents, selected through purposive sampling techniques. The instrument is a Likert scale questionnaire developed based on theories of social psychology and consumption and has been tested for validity and reliability. Data analysis uses an independent sample t-test. The research results indicate a significant difference; students living in boarding houses have higher hedonism scores. These findings suggest the need for tailored interventions for the student population to promote a more balanced lifestyle and financial awareness.